PENGARUH PERUBAHAN SOSIAL TERHADAP PENDIDIKAN KARAKTER PADA ANAK ANAK DI RT 059/RW013 PERUMNAS ROBAN - Hernandi, Riko; Okianna, Okianna; Aminuyati, Aminuyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine Social Changes towards Character Education in children in Rt 059/ Rw 013 Perumnas Roban, Central Singkawang District, Singkawang City. The research method used is descriptive quantitative research. The research sample was 42 children of Rt 059/ Rw 013. The data collected was in the form of a questionnaire consisting of four indicators, namely Social Changes in Association, Social Changes in Communication, Social Changes Due to Smartphones, and Social Changes in Self-Esteem. Based on the results of data analysis, the frequency of Social Change is 57% (24 children) in the Moderate category. Character education for children in Rt 059 / Rw 013 Perumnas Roban, Singkawang Tengah District, Singkawang City obtained a proportion of 48% (20 children), included in the medium category. The effect of social change on character education is 0.583 with a significance of 0.5%. So that the results obtained tcount ttable, namely 55,892 2,021. Furthermore, there is a positive influence between Social Change on Character Education for children in Rt 059/Rw 013 Perumnas Roban, Central Singkawang District, Singkawang City.